Ethylene glycol co-solvent enhances alkyl levulinate production from concentrated feeds of sugars in monohydric alcohols. (15th November 2021) - Yu, Xin; Peng, Lincai; Dai, Jun; Li, Hui; Tao, Chaonan; Yang, Fa; Zhang, Junhua
Graphical abstract: Highlights: Ethylene glycol co-solvent positively alters the chemoselectivity of sugar conversion. The formation of undesired polymeric humins could be greatly suppressed. An unprecedented alkyl levulinate yield of 56% was obtained from 200 g/L glucose. Improvement of processing efficiency and sustainability toward the biofuel production. Abstract: Conversion of carbohydrates at concentrated feeds represents highly desirable for the industrial deployment of biobased fuels and chemicals but challenging. One key bottleneck is that the excessive formation of polymeric humins greatly diminishes the utilization rate of feedstocks and the destination product yield. We report that the use of ethylene glycol as co-solvent for acid-catalyzed conversion of concentrated sugars enhances desirable alkyl levulinate (AL) production compared to reactions carried out in single monohydric alcohols (e.g., methanol, ethanol). Ethylene glycol served not only as a solubilizer of sugars in the reaction medium to lessen their tendency to polymerize by protecting reactive hydroxyl groups in sugars with alcohols, but also as a supporter to restrain the condensation of furan intermediates. With 10 vol% ethylene glycol as the co-solvent of ethanol, an improved yield of ethyl levulinate (EL) from 45% to 56% was accomplished from concentrated feeds of glucose (200 g/L). In particular, high space time yield and EL concentration respectively up to 30 kg/m 3 ·h and 90 g/L were obtained in a batch reactor. The solvents and catalyst could be isolated from the products, and showed good reusability. This contribution opens a reliable avenue for converting highly concentrated feeds of biomass-related sugars to oxygenated liquid fuels and versatile chemicals.